Inuit group (Ippaktuq Tasseok--"Harry"--and family) in snow house, west coast of Hudson Bay, Canada - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1897)
Five Inuit identified as probably "Harry" (Ippaktuq Tasseok) and family sit inside what appears to be a snow house. The group apparently includes two children and a woman. Lifestyle Livelihood Infrastructure Title supplied by cataloger. On mount, 5 1/2 x 6 1/2 in. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment. Harry is referred to in the North as Comer's [Captain George Comer] "mate," and was the leader of a group of Iglulik Inuit known as the Aivilik or Aivillingmiut. These Inuit of the west coast region of Hudson Bay were closely associated with Comer and the American whalers for many years.